Canonical Wnt Signaling Modulates the Expression of Pre- and Postsynaptic Components in Different Temporal Patterns - Martinez, Milka; Torres, Viviana I.; Vio, Carlos P.; Inestrosa, Nibaldo C. (My University, 2020)
Wnt ligands play critical roles in neuronal development, synapse formation, synaptic activity, and plasticity. Synaptic plasticity requires molecular remodeling of synapses, implying the expression of key synaptic components. Some studies have linked Wnt signaling activity to changes in synaptic protein levels. However, the presynaptic and postsynaptic gene expression profiles of hippocampal neurons exposed to Wnt proteins have not been studied. Hence, we treated rat cultured hippocampal neurons with recombinant Wnt3a, lithium, and the Wnt inhibitor Dkk-1 for different treatment durations and measured the mRNA and protein levels of pre- and postsynaptic components. The ligand Wnt3a promoted the differential temporal expression of genes encoding presynaptic and postsynaptic proteins. Gene expression of the presynaptic proteins Rim1, piccolo (Pclo), Erc2, Ctbp1 and Rimbp2 increased in a specific temporal pattern. Simultaneously, the mRNA and protein levels of postsynaptic components showed a different temporal expression pattern, e.g., the mRNAs for postsynaptic scaffolding components such as postsynaptic density protein-95 (PSD-95/Dlg4), Homer1 and Shank1 were temporally regulated by both Wnt3a and lithium. On the other hand, the mRNA levels of the gene encoding the protein calcium/calmodulin-dependent protein kinase IV (Camk4), canonically upregulated by Wnt, were increased. Our results suggest that Wnt signaling orchestrates expressional changes in genes encoding presynaptic and postsynaptic components, probably as part of a synaptic plasticity mechanism in neurons.
Keywords: canonical wnt signaling; genes encoding presynaptic proteins; genes encoding postsynaptic; proteins; hippocampus